2016
DOI: 10.2105/ajph.2015.303022
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Hospitalized Unintentional Injury Between Aboriginal and Non-Aboriginal Children in New South Wales, Australia

Abstract: Australian Aboriginal children suffer a disproportionately high burden of unintentional injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Identification of Aboriginal status in these data is based on self‐identification and research by the Australian Bureau of Statistics (ABS) suggests that Aboriginal people are more likely to identify in ABS data collections, such as the Census, compared with other data collections such as hospital data 4 . This is supported by findings of our previous studies which investigated injuries in a cohort of Aboriginal and non‐Aboriginal children born in a NSW hospital 5,6 . They showed larger inequalities in unintentional injury between Aboriginal and non‐Aboriginal children in New South Wales (NSW), Australia, compared with previous cross‐sectional studies using population rates 5 .…”
supporting
confidence: 81%
“…Identification of Aboriginal status in these data is based on self‐identification and research by the Australian Bureau of Statistics (ABS) suggests that Aboriginal people are more likely to identify in ABS data collections, such as the Census, compared with other data collections such as hospital data 4 . This is supported by findings of our previous studies which investigated injuries in a cohort of Aboriginal and non‐Aboriginal children born in a NSW hospital 5,6 . They showed larger inequalities in unintentional injury between Aboriginal and non‐Aboriginal children in New South Wales (NSW), Australia, compared with previous cross‐sectional studies using population rates 5 .…”
supporting
confidence: 81%
“…We used Indigenous status as recorded in birth records to minimise the effect of differential misclassification bias, whereby the opportunity to be recorded as Indigenous rises with the number of times a child is admitted to hospital. However, applying different algorithms to identify Indigenous children on the basis of linked hospital data has been shown to increase both their identification and the sizes of differences between Indigenous and non‐Indigenous children 2 , 27 . Our estimates of differences between Indigenous and non‐Indigenous children may therefore be conservative.…”
Section: Discussionmentioning
confidence: 99%
“…The linked data were used to define a cohort of children for the analysis, details of which have been described elsewhere 2 . In brief, we selected all children resident in NSW and born in a NSW hospital between 1 July 2000 and 31 December 2012.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burns are a leading cause of child morbidity and mortality in Australia 1,2 . Previous studies have shown that Indigenous children and children living in rural and remote areas are disproportionally affected by burn injuries 3,4 . A much larger proportion of Indigenous (5.1%) compared with non‐Indigenous (0.5%) children live in remote areas 5 .…”
mentioning
confidence: 99%